Exploring Gamification for Recruitment through Actor Network Theory. (December 2019) - Shree, Sonal; Singh, Ardhendu Shekhar
Abstract: This article examines the benefits of applying gamification in the recruitment process. It highlights how it can be effectively leveraged with the right design by involving various stakeholders at varied stages. The Actor Network Theory (ANT) as a theoretical ground has been used as a reference point to take a more detailed look at the ways in which gamification can be effectively deployed for recruitment by organizations. We refer to ANT and the interaction between the human and non-human elements, here, the applicants, the other stakeholders, and the gamification tools, to serve the greater organizational purpose. Questions that interrogate between rules and practices arise, viz. can the game be effectively customized to achieve sophisticated and enhanced selection outcomes. By applying gamification as the reference point within the Actor Network Theory, their associated potential for further research and applications is achieved. A valuable perspective in gaining insights for further understanding of this theory in today's technologically progressive environment has also been discussed for further reflection.